Improving the Discipline Character of Students Through the Implementation of the Students’ Handbook - Munasir, Munasir; Mahmudin, Wildan; Ramdani, Miswan; Badrudin, Badrudin; Zaqiah, Qiqi Yuliati (EDUTEC : Journal of Education And Technology, 2024)
The issue of disciplinary practices among students in Islamic boarding schools (pesantren) is an important topic that needs to be examined. The phenomenon of student behavior that shows a lack of discipline or is far from the values of discipline has affected the teaching and learning process in pesantren. This study aims to describe the implementation of the student handbook as an effort to improve student discipline. This research uses a qualitative method with a case study approach, involving data collection techniques through interviews, observations, and documentation. The focus of this research is to understand how the student handbook is implemented and its effectiveness in improving student discipline. The implementation model used is the MUNASIR model, which includes Modelling, Universal, Natural, Action, Socialization, Internalization, Reward, and Punishment. The results of the study show that the implementation of the student handbook with the MUNASIR model is effective in improving student discipline in pesantren. Through this approach, students become more aware of the importance of discipline and show improved disciplined behavior in their daily lives at the pesantren. This study contributes to the development of more systematic and structured strategies for improving student discipline in Islamic boarding schools